2016
DOI: 10.1017/s147474561600029x
|View full text |Cite
|
Sign up to set email alerts
|

Servicification of Firms and Trade Policy Implications

Abstract: In the OECD countries, the decline of manufacturing and the employment implications have long been matters of concern. Recently, policymakers in several countries have set out to try and achieve reindustrialization. The servicification of firms is related to these concerns and aspirations. However, servicification, and particularly its role in trade policy, has received limited attention. I review micro-level evidence and discuss its implications. I find that imported, domestic and exported services are all im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 89 publications
5
21
0
2
Order By: Relevance
“…Increasingly from the view of international trade and economic growth, services are observed to be closely linked with the manufacturing activities. As opposed to the traditional belief that the manufacturing sectors are relatively independent of service sectors, the recent trends in OECD countries have revealed that manufacturing industries are increasingly using services in production as well as selling services directly to the consumers (Boddin & Henze, 2014;Lodefalk 2017;OECD 2014). The increasing use, production and sales of services in manufacturing sectors are described as the "servicification" of manufacturing (Elms & Low, 2013;Lodefalk, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly from the view of international trade and economic growth, services are observed to be closely linked with the manufacturing activities. As opposed to the traditional belief that the manufacturing sectors are relatively independent of service sectors, the recent trends in OECD countries have revealed that manufacturing industries are increasingly using services in production as well as selling services directly to the consumers (Boddin & Henze, 2014;Lodefalk 2017;OECD 2014). The increasing use, production and sales of services in manufacturing sectors are described as the "servicification" of manufacturing (Elms & Low, 2013;Lodefalk, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Servicification is crucial for the manufacturing sectors for multiple reasons. First, as "enablers" of the GVCs, services are increasingly used in developing countries to participate, connect and benefit from the global economy (Lodefalk, 2017). For example, the call centres in India and Philippines provide low-cost services for overseas manufacturing firms in GVCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Services are also embedded in goods that are traded internationally (Cernat 2015): they include, for example, logistics, design, engineering or accounting that are necessary inputs in the manufacturing process. This type of trade is referred to as the 'servicification of manufacturing' (Lanz and Maurer 2015;Lodefalk 2017). In Europe, it is estimated to be worth over €300 billion and accounts for about one third of total EU goods exports (Cernat 2015).…”
Section: Trade In the Twenty-first Centurymentioning
confidence: 99%
“…Services account for the major share of employment and value added, and this share is continually growing (World Bank, ). However, exports of services are subject to substantially higher trade costs than are merchandise exports (Lodefalk, ; Miroudot, Sauvage, & Shepherd, ). Thus, services exports are increasing despite the current trade environment, not because of it.…”
Section: Introductionmentioning
confidence: 99%